Rehabilitation of Stroke Survivors with Disabilities in Low- and Middle-Income Countries: Barriers and Opportunities (Journal of Enam Medical College, 2025)
Globally, stroke is a leading cause of mortality and disability and there are substantial economic costs for post-stroke care. Barriers to the rehabilitation of stroke survivors with disabilities in low- and middle-income countries are many. There are enormous challenges in overcoming the barriers. The socioeconomic impacts of disabilities are high. Developing and delivering cost-effective rehabilitation services to stroke survivors with disabilities are daunting challenges to low- and middle-income countries. The barriers and unmet needs for rehabilitation treatments are high. These challenges are amplified by resource constraints like infrastructural facilities for rehabilitation management, and an inadequately trained healthcare workforce in low- and middle-income countries (LMICs). Multidisciplinary team care management led by physicians, therapists, rehabilitation nurses, and community health workers need to be strengthened. Threats to the outcomes of stroke care in resource-poor settings are the non-availability of cost-effective team care at the hospital and at the community level.   Long-term medical and rehabilitation care needs organizational and financial support.  The future challenge is to identify what elements of organized stroke care can be implemented to make the largest gain.  Simple interventions such as swallowing assessments, bowel and bladder care, mobility assessments, and consistent secondary prevention can prove to be key elements to improving post-discharge morbidity and mortality. Recognition of the importance of stroke rehabilitation by WHO and global health leaders are new opportunities for LIMCs to fight back the stroke-related disabilities. Successful rehabilitation of stroke survivors with disabilities is a paramount challenge in LIMCs. But opportunities are coming up as there is increased awareness about stroke among general people. Task shifting of the rehabilitation health workforce to caregivers at the home or community level can help augment disability-adjusted life years. Proper Caregivers Training is coming out as a good prognostic indicator in stroke survivors in low resource settings. Structured training of caregivers is essentially needed at the low resource outset in developing countries and should be emphasized in stroke rehabilitation protocol.   Universal health coverage should be extended to poor stroke survivors with disability.   The burden of stroke will further increase until effective stroke prevention strategies are more widely implemented. The objective of this review article is to highlight the elements of health system behavior that affect barriers and opportunities in addressing stroke survivors with disabilities.J Enam Med Col 2022; 12(3): 148−154